INTEGRATED MARKETING COMMUNICATION (IMC)-BASED REBRANDING STRATEGY FOR BUILDING BRAND AWARENESS: A CASE STUDY OF SMARTONE SOLO - Dani Setiawan; Tina Kartika (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study aims to analyze the rebranding communication strategy implemented by SmartOne Solo branch following the change of ownership from Printex Solo. The rebranding was driven by differences in vision and mission between the two owners after two years of operation, which ultimately led to a full acquisition by SmartOne and a change in brand identity. This research employs a qualitative approach with a case study method and a constructivist paradigm to understand the process of constructing new meaning through communication between the company and the public. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the rebranding communication strategy was carried out through systematic stages, including internal alignment, identity transformation, external communication, IMC implementation, and brand reinforcement. This communication integration reflects the application of Integrated Marketing Communication (IMC), which emphasizes message consistency and coordination across communication channels. The communication strategy has proven to effectively increase public brand awareness of SmartOne Solo, as indicated by the growing recognition and use of the brand name in daily interactions. This study confirms that the success of rebranding is not solely determined by changes in visual identity, but also by the effectiveness of an integrated, consistent, and sustainable communication strategy.